Pattern of Visit by Butterflies in Different Time Frames on Lantana camara Linnaeus in Urban Landscapes of Kolkata - Dutta, Ritam; Mitra, Sayantan (Asian Journal of Biological and Life Sciences, 2017)
Plant insect interaction is a healthy phenomenon in the nature. In the urbanised area, butterfly and flowering plant interaction indicates the status of environment of such area. Lantana camara Linnaeus is an invasive plant with a great negative impact to the nature but the butterfly association with this plant also has a great impact for holding biodiversity.A work was conducted to study the association of butterflies with Lantana camara Linnaeus in different time frame viz. 6-8 am, 8-10am, 10am-12pm, 12-2pm, 2-4pm and 4-6pm. A total number of 24 species of butterflies belonging to 4 sub families has been reported from this plant. Among these six time frames 8-10am holds significantly highest butterfly visitors (χ²=11.96296, df=5, p =0.035312). Visitations of different butterfly families also have been studied and study shows different pattern of visit for different family in each time frame.
Keywords: Butterfly; Lantana camara Linnaeus; Urban ecosystem; Visitation pattern